2012
DOI: 10.4103/0972-2327.104348
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin in the treatment of drug rash eosinophilia and systemic symptoms caused by phenytoin

Abstract: A 32 year old Asian female on 300 mg per day of phenytoin following meningioma excision developed a fever with a diffuse maculopapular rash, lymphadenopathy and splenomegaly after12 days. A diagnosis of DRESS (Drug Rash Eosinophilia and Systemic Symptoms) syndrome was made. Patient was started on prednisolone at a dose of 1 mg/kg but since there was further deterioration in her condition, intravenous immunoglobulin was started. Clinical and blood parameters began to improve by the next day with liver functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…12 IVIG has been successfully combined with corticosteroids and may have a role in cases refractory to systemic steroid administration. 3,7,8 Drug reaction with eosinophilia and systemic symptoms syndrome is thought to be a T cell-mediated reaction related to human leukocyte antigen (HLA) type and racial factors. 13 It is hypothesized to occur in individuals with drug detoxification defects that lead to an increase in reactive metabolites and subsequent immunologic reaction coupled with reactivation of specific viruses such as HHV-6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 IVIG has been successfully combined with corticosteroids and may have a role in cases refractory to systemic steroid administration. 3,7,8 Drug reaction with eosinophilia and systemic symptoms syndrome is thought to be a T cell-mediated reaction related to human leukocyte antigen (HLA) type and racial factors. 13 It is hypothesized to occur in individuals with drug detoxification defects that lead to an increase in reactive metabolites and subsequent immunologic reaction coupled with reactivation of specific viruses such as HHV-6.…”
Section: Discussionmentioning
confidence: 99%
“…Although the benefits of IVIG treatment in severe adverse drug reactions have not been completely Despite the potential benefits of IVIG, its effectiveness as an adjunct to systemic corticosteroids in steroid hyporesponsive DRESS syndrome remains unclear. Although IVIG has been successfully used to treat adults, 3,5,7,8 in one recent study, most patients suffered severe adverse effects. 9 However, a recent pediatric study showed minimal adverse effects of IVIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient experienced mild DRESS syndrome, therefore resolution of signs and symptoms could not be ascribed to prednisone without reserve. High-dose intravenous immunoglobulin therapy has been established by various experts in USA as the first line treatment of DRESS syndrome and Toxic epidermal necrolysis based on findings that intravenous immunoglobulins can reduce Fas-FasL interaction [15,16].…”
Section: Discussionmentioning
confidence: 99%